An objective‐based prioritization approach to support trophic complexity through ecological restoration species mixes. Issue 2 (5th July 2021) - Ladouceur, Emma; McGowan, Jennifer; Huber, Patrick; Possingham, Hugh; Scridel, Davide; van Klink, Roel; Poschlod, Peter; Cornelissen, Johannes Hans C.; Bonomi, Costantino; Jiménez‐Alfaro, Borja
Abstract: Reassembling ecological communities and rebuilding habitats through active restoration treatments require curating the selection of plant species to use in seeding and planting mixes. Ideally, these mixes should be assembled based on attributes that support ecosystem function and services, promote plant and animal species interactions and ecological networks in restoration while balancing project constraints. Despite these critical considerations, it is common for species mixes to be selected opportunistically. Reframing the selection of seed mixes for restoration around ecological objectives is essential for success but accessible methods and tools are needed to support this effort. We developed a framework to optimize species seed mixes based on prioritizing plant species attributes to best support different objectives for ecosystem functions, services and trophic relationships such as pollination, seed dispersal and herbivory. We compared results to approaches where plant species are selected to represent plant taxonomic richness, dominant species and at random. We tested our framework in European alpine grasslands by identifying 176 plant species characteristic of the species pool, and identified 163 associated attributes affiliated to trophic relationships, ecosystem functions and services. In all cases, trophic relationships, ecosystem functions and services can be captured more efficiently through objective‐based prioritization using the functional identity of plant species. Solutions (plant species lists) can be compared quantitatively, in terms of costs, species or objectives. We confirm that a random draw of plant species from the regional plant species pool cannot be assumed to support other trophic groups and ecosystem functions and services. Synthesis and Applications . Our framework is presented as a proof‐of‐concept to help restoration practitioners better apply quantitative decision support to plant species selection to efficiently meet ecological restoration outcomes. Our approach may be tailored to any restoration initiative, habitat or restoration targets where seeding or planting mixes will be applied in active treatments. As global priority and resources are increasingly placed into restoration, this approach could be advanced to help make efficient decisions for many stages of the restoration process. Abstract : Our framework is presented as a proof‐of‐concept to help restoration practitioners better apply quantitative decision support to plant species selection to efficiently meet ecological restoration outcomes. Our approach may be tailored to any restoration initiative, habitat or restoration targets where seeding or planting mixes will be applied in active treatments. As global priority and resources are increasingly placed into restoration, this approach could be advanced to help make efficient decisions for many stages of the restoration process.